Integrated sectors - diversified earnings: The (missing) impact of offshoring on wages and wage convergence in the EU27 - Aleksandra Parteka; Joanna Wolszczak-Derlacz (Gdańsk University of Technology, Faculty of Management and Economics, 2014)
This paper assesses the impact of international outsourcing/offshoring practices on the process of wage equalization across manufacturing sectors in a sample of EU27 economies (1995-2009). We discriminate between heterogeneous wage effects on different skill categories of workers (low, medium and high skill). The main focus is on the labour market outcomes of vertical integration, so we augment a model of conditional wage convergence through the inclusion of sector-specific broad and narrow outsourcing/offshoring indices based on input-output data (World Input Output Database, April 2012 release). Two-way relations between trade and wages are addressed through the use of a gravity-based sector-level instrument. We find no evidence supporting unconditional skill-specific wage convergence in EU sectors. In a conditional setting, (slow) wage convergence takes place, but international outsourcing plays a negligible role in wage equalization. Moreover, even though regression results indicate that offshoring reduces the wage growth of domestic medium- and low-skilled workers, we show that this negative effect is economically small.
Keywords: F14; F16; F66; C67; 330; wage; convergence; international outsourcing; offshoring; input-output